1999
DOI: 10.1017/s0022226798007312
|View full text |Cite
|
Sign up to set email alerts
|

Telling general linguists about Altaic

Abstract: The hypothesis of an Altaic language family, comprising the Turkic, Mongolic, Tungusic, Korean and, in most recent versions, Japanese languages continues to be a viable linguistic proposal, despite various published claims that it is no longer accepted. A strong body of research continues to appear, developing and refining the hypothesis, along with publications that argue against a demonstrated relationship among these languages. This paper shows that many of the arguments against a genetic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Social and academic interest in orthodontics is increasing in Mongolia, but there are no data available in orthodontic or other professional journals concerning cephalometric standards for the Mongolian population. Various anthropological studies have reported linguistic 19 and genetic [20][21][22][23][24] associations between Mongolians and Koreans, but cephalometric comparisons between the two related ethnic groups have not been reported. The purposes of this study were (1) to establish the cephalometric norms of men and women adults from Mongolia who were selected on the basis of having normal occlusions and well-balanced profiles, and (2) to compare them with the cephalometric norms of the Korean samples selected with the same process.…”
Section: Introductionmentioning
confidence: 99%
“…Social and academic interest in orthodontics is increasing in Mongolia, but there are no data available in orthodontic or other professional journals concerning cephalometric standards for the Mongolian population. Various anthropological studies have reported linguistic 19 and genetic [20][21][22][23][24] associations between Mongolians and Koreans, but cephalometric comparisons between the two related ethnic groups have not been reported. The purposes of this study were (1) to establish the cephalometric norms of men and women adults from Mongolia who were selected on the basis of having normal occlusions and well-balanced profiles, and (2) to compare them with the cephalometric norms of the Korean samples selected with the same process.…”
Section: Introductionmentioning
confidence: 99%
“…The third, fifth, sixth, seventh, and eighth of these families are sometimes related by various versions of the Altaic hypothesis, which asserts a genetic relation between Mongolic, Tungusic, and Turkic (Ramstedt 1952) or between these three families and Koreanic (Poppe 1960) and Japonic (Starostin et al 2003;Robbeets 2005). However, there is still no scholarly consensus about the Altaic hypothesis; for critiques, see Georg et al (1999) and Vovin (2005), among many others. 1 Food production in Northeast Asia ranges from wet rice cultivation in Korea and Japan to steppe pastoralism in Mongolic and Turkic language areas, to reindeer pastoralism among speakers of Kamchukotic, Yeniseic, Yukaghiric, and Tungusic, to hunting and fishing among these groups and Ainuic.…”
Section: Introductionmentioning
confidence: 99%
“…There are researchers who group Korean and Japanese as part of an even greater family—Altaic. The macro-Altaic hypothesis (we use the term ‘macro-Altaic’ to refer to the Altaic hypothesis that includes Tungusic, Mongolic, Turkic, Japanese, Ainu and Korean, as opposed to simply ‘Altaic’ or ‘micro-Altaic’ that only covers Tungusic, Mongolic and Turkic) also includes Mongolian and Turkish [51]. Glottolog, which was used as the information source for linguistic genealogy in this paper, does not place Korean and Japanese in the same family, nor does the Ethnologue.…”
Section: Resultsmentioning
confidence: 99%